The effect of Phytopaj )Ferula assa-foetida L. oleo gum resin and tragacanth( in patients with COVID-19: A randomized clinical trial - Hamid Reza Bahrami-Taghanaki; Hamidreza Hoseinzadeh; Shokouhsadat Hamedi; Majid Jafari Nejad-Bajestani; Nayereh Esmaeilzadeh; Hasan Abdollahzadeh; Seyedehmasoume Hoseini-asil; Gholamreza Haghighi; Amin Bojdi (Mashhad University of Medical Sciences, 2024)
Objective: Exogenous hydrogen sulfide (H2S) has a positive effect on respiratory diseases. Oleo-gum of Ferula assa-foetida contains this compound. This study assessed the effects of Ferula assa-foetida L. oleo gum resin and tragacanth (Phytopaj) on patients with COVID-19. Materials and Methods: A randomized, single-blinded, controlled trial (RCT) phase 2 was conducted in Mashhad on hospitalized COVID-19 patients. In this RCT, 122 patients were randomly assigned to either receive a 14-day oral phytopaj plus ordinary treatment or ordinary treatment only. Changes in peripheral blood lymphocyte count (LC) and blood oxygen saturation (PO2) were the endpoints. Results: Mean±SD of PO2 in Phytopaj comparison ordinary treatment before intervention was 91.86±4.62 and 91.41±9.18, after the intervention it was 93.22±4.26 and 91.91±5.92 mmHg; before intervention, mean±SD of peripheral blood lymphocyte count was 1015.90±500.55, and 1104.28±543.61, and after intervention, it was 1652.27±921.38 and 1326.12±719.28/μL respectively. Participants' age, comorbidity, gender, and stage ofConclusion: Phyopaj is most useful in moderate stages of Covid19, and it is not recommended for elderly patients and patients with comorbidity until more insight is gained.